Vision & values in design management - Hands, David (Switzerland AVA Academia, 2009)
Examines the nature and value of design from a range of global perspectives. This work explores the relationship between design leadership and management and the application and value of design in the face of future challenges.
Keywords: Industrial design -- Management -- Case studies; Industrial design -- Management; Industrial design -- Moral and ethical aspects